2020
DOI: 10.1002/jcp.29631
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐377 acts as a suppressor in esophageal squamous cell carcinoma through CBX3‐dependent P53/P21 pathway

Abstract: Stem cells play pivotal roles in esophageal squamous cell carcinoma (ESCC) recurrence and metastasis. The self-renewal ability of stem cells was associated with specific microRNAs (miRs). Herein, we identified the effects of miR-377 on ESCC stem cell activities. First, the expression of miR-377 in ESCC and adjacent normal tissues was determined. The relationship between miR-377 and chromobox protein homolog 3 (CBX3) was assessed by a dual-luciferase reporter gene assay. miR-377 was overexpressed or inhibited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…11 CBX3 is normally not detected in differentiated cells of various normal human tissues, but is detected in tumor tissues of various cancers, including esophageal, lung, cervical, colon, and breast cancers. [12][13][14][15] Substantial evidence indicates that CBX3 has cancerogenic and prognostic roles in various cancer types. However, the exact functions of CBX3 in HNSCC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…11 CBX3 is normally not detected in differentiated cells of various normal human tissues, but is detected in tumor tissues of various cancers, including esophageal, lung, cervical, colon, and breast cancers. [12][13][14][15] Substantial evidence indicates that CBX3 has cancerogenic and prognostic roles in various cancer types. However, the exact functions of CBX3 in HNSCC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CBX3 is significantly upregulated in osteosarcoma tumor stem cells and facilitates their self-renewal [ 48 ]. Also, He Z. et al [ 49 ] have reported that esophageal squamous cell carcinoma (ESCC) acquire stem cell-like characteristics through CBX3-dependent inactivation of p53/p21 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Aurora Kinase A, encoded by AURKA, is implicated in cell mitosis process, including centrosome maturation and spindle formation [ 44 , 45 ]. The anti-leukemic effect of Aurora kinase inhibitors was reported via inducing mitochondrial impairment [ 46 ], cell cycle arrest[ 47 ] etc. Preliminary clinical studies have been conducted to validate the efficacy and safety of Aurora kinase inhibitors in AML [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%